Profiling the Anaerobic Response of C. elegans Using GC-MS - Butler, Jeffrey A.; Mishur, Robert J.; Bokov, Alex F.; Hakala, Kevin W.; Weintraub, Susan T.; Rea, Shane L. (PLOS ONE, 2012)
The nematode Caenorhabditis elegans is a model organism that has seen extensive use over the last four decades in multiple areas of investigation. In this study we explore the response of the nematode Caenorhabditis elegans to acute anoxia using gas-chromatography mass-spectrometry (GC-MS). We focus on the readily-accessible worm exometabolome to show that C. elegans are mixed acid fermenters that utilize several metabolic pathways in unconventional ways to remove reducing equivalents – including partial reversal of branched-chain amino acid catabolism and a potentially novel use of the glyoxylate pathway. In doing so, we provide detailed methods for the collection and analysis of excreted metabolites that, with minimal adjustment, should be applicable to many other species. We also describe a procedure for collecting highly volatile compounds from C. elegans. We are distributing our mass spectral library in an effort to facilitate wider use of metabolomics.